Strategic agility-enabled business model innovation :|a multi-method study - Albayraktaroğlu, Alptegin. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2022., 2022)
Strategic agility (SA) enables adaptation in turbulent environments by accelerating business model renewal. However, despite its critical role as a dynamic capability, relatively little is known about the relationship between the set of capabilities underlying SA and business model innovation (BMI) for different BMI initiatives and contextual characteristics. Against this backdrop, this dissertation investigates 1-the capability combinations that enable business model innovation for different BMI initiatives, and 2-the implications of firm size, environmental turbulence, and structural embeddedness as contextual conditions for the SA-BMI relationship and BMI performance. The study adopts multiple methods to address these issues. In Study 1, a multiple-case study featuring four companies has been conducted to analyze the role of SA-related capabilities in the BMI process. By reflecting the temporal deployment of the SA-related capabilities along the phases of BMI at the case firms, the study sheds light on how organizations design and implement new business models by leveraging strategic agility. In Study 2, a fuzzy set qualitative comparative analysis (fsQCA) has been conducted to explore the role of firm size, environmental turbulence, and structural embeddedness as contextual characteristics in the SA-BMI relationship and BMI performance in a sample of service firms. The contribution of this study is that it provides a comprehensive analysis of the organizational and contextual enablers of the effective pursuit of BMI through a multi-method study that takes the process dynamics and the alternative paths into consideration.
Keywords: Strategic planning.; Business planning.